Waveguide Concentrator Photovoltaic with Spectral Splitting for Dual Land Use - Hoang Vu; Tran Quoc Tien; Jongbin Park; Meeryoung Cho; Ngoc Hai Vu; Seoyong Shin (Energies, 2022)
This research presents a highly transparent concentrator photovoltaic system with solar spectral splitting for dual land use applications. The system includes a freeform lens array and a planar waveguide. Sunlight is first concentrated by the lens array and then reaches a flat waveguide. The dichroic mirror with coated prisms is located at each focused area at the bottom of a planar waveguide to split the sunlight spectrum into two spectral bands. The red and blue light, in which photosynthesis occurs at its maximum, passes through the dichroic mirror and is used for agriculture. The remaining spectrums are reflected at the dichroic mirror with coated prisms and collected by the long solar cell attached at one end of the planar waveguide by total internal reflection. Meanwhile, most of the diffused sunlight is transmitted through the system to the ground for agriculture. The system was designed using the commercial optic simulation software LightTools™ (Synopsys Inc., Mountain View, CA, USA). The results show that the proposed system with 200<semantics>×</semantics> concentration can achieve optical efficiency above 82.1% for the transmission of blue and red light, 94.5% for diffused sunlight, which is used for agricultural, and 81.5% optical efficiency for planar waveguides used for power generation. This system is suitable for both high Direct Normal Irradiance (DNI) and low DNI areas to provide light for agriculture and electricity generation at the same time on the same land with high efficiency.